Junior High School Educators’ Strategies for Making Inclusive Education Policy a Working Tool in the Kadjebi District, Ghana (Global Journal of Human-Social Science, 2025)
Background Like all children persons with disability need quality of education to develop their skills and realize their full potential Yet they are often overlooked in policymaking limiting their access to education and their ability to participate in social economic and political life Objective The study aims at investigating JHS educators strategies for making inclusive education policy a working tool in the Kadjebi District Ghana Methods A cross-sectional descriptive design was employed with 191 JHS educators Data were analysed using frequency distribution and percentages Kappa statistics and multiple linear regressions Results Educators that build a welcoming school environment was statistically significant at P 0 000 coeff 1 000 95 CI 1 000 1 000 Educators confident to teach children with special needs was statistically significant at P 0 000 coeff -0 250 95 CI -0 250 -0 250 Being ignorant about pupils with special education needs in classroom was statistically significant at P 0 000 coeff 0 600 95 CI 0 600 6 00 Educators being able to provide adequate learning facilities at home was statistically significant at P 0 000 coeff - 1 000 95 CI -1 000 -1 000 Conclusion The study recommends that educators should be encouraged to adjust their perceptions and attitudes towards children with disability in their schools so that they can own out to nurture them well
Keywords: disability; education; educators; inclusion; inclusive; policy; special education; strategy